2015
DOI: 10.1039/c5nr03133h
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced second harmonic generation of MoS2layers on a thin gold film

Abstract: The linear and nonlinear optical properties of thin MoS2 layers exfoliated on an Au/SiO2 substrate were investigated both numerically and experimentally. It was found that the MoS2 layers with different thicknesses exhibited different colors on the gold film. The reflection spectra of the MoS2 layers with different thicknesses were calculated by using the finite-difference time-domain technique and the corresponding chromaticity coordinates were derived. The electric field enhancement factors at both the funda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 44 publications
0
40
0
Order By: Relevance
“…173 Zeng et al demonstrated that SHG of few layers MoS 2 can be enhanced by simply placing MoS 2 on a gold film. 172 They found that F I G U R E 6 A, SHG mapping of monolayer MoS 2 . 160 Copyright 2018, American Chemical Society.…”
Section: Optical Cavity-enhanced Nlomentioning
confidence: 99%
See 3 more Smart Citations
“…173 Zeng et al demonstrated that SHG of few layers MoS 2 can be enhanced by simply placing MoS 2 on a gold film. 172 They found that F I G U R E 6 A, SHG mapping of monolayer MoS 2 . 160 Copyright 2018, American Chemical Society.…”
Section: Optical Cavity-enhanced Nlomentioning
confidence: 99%
“…Copyright 2016, American Chemical Society. D, Au film‐enhanced SHG of few layers MoS 2 . Copyright 2015, The Royal Society of Chemistry.…”
Section: Modulation and Enhancement Of Nlomentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, an exceedingly large two-photon absorption coefficient (larger than that of conventional semiconductors by three orders of magnitude) and a large laser damage threshold of single layer MoS 2 island were reported [20]. SHG and third harmonic generation from single or few layers MoS 2 film were also reported [21][22][23]. MoS 2 nanosheets are expected to be NIR-excited optical nanoprobes for bioimaging.…”
Section: Introductionmentioning
confidence: 99%